2013
DOI: 10.1002/qre.1544
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Monitoring Ecological Systems—A Statistical Process Control Approach

Abstract: Statistical process control monitoring of nonlinear relationships (profiles) has been the subject of much research recently. While attention is primarily given to the statistical aspects of the monitoring techniques, little effort has been devoted to developing a general modeling approach that would introduce ‘uniformity of practice’ in modeling nonlinear profiles (analogously with the three‐sigma limits of Shewhart control charts). In this article, we use response modeling methodology (RMM) to demonstrate imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Mo et al [10] used an SPC control chart to monitor the process deterioration caused by vibration in the manufacturing. An SPC control chart can also be applied to monitor the ecological system Shore [11]. This research demonstrated that SPC is a time-based out-of-limit detection system.…”
Section: Time Domain Analysis Methodsmentioning
confidence: 92%
“…Mo et al [10] used an SPC control chart to monitor the process deterioration caused by vibration in the manufacturing. An SPC control chart can also be applied to monitor the ecological system Shore [11]. This research demonstrated that SPC is a time-based out-of-limit detection system.…”
Section: Time Domain Analysis Methodsmentioning
confidence: 92%
“…The basic approach for monitoring the LP is a regression‐adjusted scheme, where only residuals are monitored using regular Shewhart charts (refer for a summary of regression‐adjusted control and its origins to, for example, Shore). Effectiveness evaluation is carried out by comparing obtained ARL values to those that would have been obtained, using same data, if the ‘true model’ (the data generating model) was used for modeling and monitoring.…”
Section: Evaluating Performancementioning
confidence: 99%